KAPABILITAS PEMERINTAH DESA DALAM PEMBANGUNAN DI DESA PAMBANG PESISIR KABUPATEN BENGKALIS PROVINSI RIAU TAHUN 2022 - Alif, Muhammad Nur; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research was motivated by the village government carrying out activities for village infrastructure development. So, in developing village infrastructure, efforts are needed to meet planned development needs, namely increasing institutional capabilities, human resources, policy implementation, finance, technical and leadership. The problem formulation in this research aims to determine and explain the Village Government's Capabilities in Development in Pambang Pesisir Village, Bengkalis Regency, Riau Province in 2022. This research is field research, carried out in Pambang Pesisir village, Bengkalis Regency. To obtain the results in this research, the author used Kusumasari's capability theory. There are 6 indicators carried out, namely, Institutional, Human Resources, Financial, Policy Implementation, Technical, Leadership. This research uses qualitative methods with descriptive research type. The types of data used in this research are primary data and secondary data, the data sources used come from the Pambang Pesisir Village Office and informants. Data collection techniques were carried out using interviews and documentation. The research results show that the Pambang Pesisir Village Government has an important role in village development and there is participation from the village community so that village development runs as expected. Keywords: Institutions, Human Resources, Policy Implementation, Finance, Technical, Leadership.